Dedifferentiated Central Chondrosarcoma: A Clinical, Histopathological, and Immunohistochemical Analysis of 57 Cases - Gong, Li-Hua; Su, Yong-Bin; Zhang, Wen; Liu, Wei-Feng; Dong, Rong-Fang; Sun, Xiao-Qi; Zhang, Ming; Ding, Yi (Frontiers in Medicine, 2021)
Dedifferentiated central chondrosarcoma (DCCS) is a rare cartilage tumor with invasive biological behavior and a poor prognosis. To better understand the morphological characteristics of this type of tumor and its internal mechanism of dedifferentiation, we retrospectively analyzed 57 cases of DCCS. A total of 29 female and 28 male patients were included, ranging in age from 20 to 76 years, with a median age of 54 years. Fifty-seven cases of DCCS occurred in the pelvis (n=29), femur (n=17), scapula (n=4), tibia (n=2), humerus (n=2), metatarsals (n=1), fibula (n=1), and radius (n=1). Radiologically, DCCS had two different appearances on imaging, with an area showing calcifications of the cartilage forming the tumor juxtaposed to a lytic area involving a highly aggressive, noncartilaginous component. Histopathologically, the distinctive morphological features consisted of two kinds of defined components: a well-differentiated cartilaginous tumor and noncartilaginous sarcoma. The cartilaginous components included Grade 1 (38, 66.67%) and Grade 2 (19, 33.33%) cartilage. The sarcoma components included osteosarcoma (29, 50.88%), undifferentiated pleomorphic sarcoma (20, 35.09%), rhabdomyosarcoma (3,5.26%), fibrosarcoma (2, 3.51%), spindle cell sarcoma (2,3.51%) and angiosarcoma (1, 1.75%). Immunohistochemistry showed that the expression of p53 and RB in the sarcoma components was significantly higher than that in the cartilaginous components, suggesting that these factors play roles in the dedifferentiation process of chondrosarcoma. DCCS is a highly malignant tumor with a poor prognosis. Except for the patients who were lost to follow-up, most of our patients died.